Application of Government Accounting Standards and Internal Control System to the Quality of Local Government Financial Statements with Human Resources Quality as a Moderation Variable (case study on Bangkinang Hospital) - Pirman Syah; Desti Monika Uli. S2; Dessy Kumala Dewi; Rani Munika; Helmiati (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to determine the effect of the implementation of Government Accounting Standards, internal control systems, and the quality of human resources on the quality of financial statements at the Bangkinang Regional General Hospital (RSUD). Sampling was carried out using a saturated sampling method with a total of 38 respondents who were employees of the finance department of Bangkinang Hospital. The data used is primary data obtained through the distribution of questionnaires to respondents. Data was collected through a questionnaire and analyzed using the Partial Least Square (PLS) method. The results of the study show that the quality of human resources has a positive and significant effect on the quality of local government financial statements. Meanwhile, the implementation of Government Accounting Standards and Internal Control Systems does not have a significant direct effect on the quality of financial statements. The results of the moderation variable test showed that the quality of human resources was able to moderate the effect of the implementation of Government Accounting Standards on the quality of financial statements, but was unable to moderate the influence of the Internal Control System on the quality of financial statements. These findings indicate that the quality of local government financial statements is not only determined by the existence of standards and systems, but also depends on the competence of the apparatus as the main implementer of financial management. This research is expected to make a theoretical contribution to the development of public sector accounting studies and become a practical consideration for local governments in an effort to improve the quality of financial statements through strengthening the quality of human resources.